Development of RapidHIT® ID using NGMSElect™ Express chemistry for the processing of reference samples within the UK criminal justice system. (February 2019) - Shackleton, David; Gray, Nicola; Ives, Lesley; Malsom, Simon; Vanhinsbergh, Des
Highlights: Development and optimisation of RapidHIT ® ID protocols with AmpFℓSTR ® NGMSElect™ Express STR kit. Demonstrated full concordance for reference data. Optimal sensitivity with RapidHIT ® ID achieved. Abstract: The RapidHIT ® ID is a new instrument which has been designed specifically for non-technical users in non-laboratory environments, for example police custody suites or border control. The development studies presented here were performed using the AmpFℓSTR ® NGMSElect™ Express STR kit with single source reference samples. The system has been successfully optimised for extraction, PCR and electrophoresis. Once optimised studies on sensitivity, in terms of DNA input template, sample repeatability and instrument reproducibility have shown that the instrument is capable of producing robust profiles within an 85 min, window, using mock reference buccal samples. This work has been carried out within the validation framework provided by the United Kingdom Forensic Science Regulator and is a key stage in the validation of the RapidHIT ® ID for use in custody suites within the UK criminal justice system.